Pengaruh Program Makan Siang terhadap Asupan Makanan, Status Anemia dan Perilaku Gizi Santri Perempuan - Dewi Kusumawati; Rimbawan Rimbawan; Ikue Ekayanti (Faculty of Public Health, Hasanuddin University, Makassar, 2019)
Provision of food in dormitories is generally limited due to cost problems so students are vulnerable tomalnutrition. Iron deficiency in adolescents can cause anemia. This study aimed to evaluate effect of lunch programon food intake, anemia status and nutritional behaviour for female students at the Darusalam Islamic BoardingSchool Bogor. This study was a pre-experiment with one group design before intervention. Selected subjectswere 54 students given interventions of adding protein and fruit at lunch and nutrition education for 15 weeks.Nutrition education delivered by the teacher and refreshment material by nutrition students. The results showedenergy, protein, fat, carbohydrate, fiber, calcium, zinc, iron and Vitamin C increased in lunch intake and differedsignificantly from before intervention (p<0.05). Nutritional status (BMI/U) increased and differed significantlybefore and after the intervention (p<0.05). The proportion of anemia status increased to be better and significantlyhigher than the comparison but increased hemoglobin levels of 0.14±1.12 g/dl have not been able to provide asignificant average hemoglobin level (p>0.05). Knowledge and nutritional attitudes of students about anemia weresignificantly different between before and after intervention (p<0.05).